JAKARTA AND GREATER KUALA LUMPUR URBAN HEAT ISLAND DURING THE PANDEMIC OF COVID-19 - Mohd Hairy bin Ibrahim (Tanjung Malim, 2024)
JAKARTA AND GREATER KUALA LUMPUR URBAN HEAT ISLAND DURING THE PANDEMIC OF COVID-19 by Mohd Hairy bin Ibrahim